Effect of acid pretreatments with various acid types on gelling properties and identification characteristics of pigskin gelatin - Zi-Xuan Yang; Xiao-Mei Sha; Hui Wang; Ting Fang; Sheng Shu; Zong-Cai Tu (Food Chemistry: X)
In order to study the effects of different types of acid pretreatment of pigskin on the gel characteristics and traceability aspects of the extracted gelatin, the molecular weight distribution and gelling properties of pigskin gelatin were studied using SDS-PAGE, texture analyzer, and rheometer. The characteristic peptides digested from pigskin gelatin were studied by HPLC-MS/MS technique. The findings revealed that gelatin extracted from pigskin pretreated with acetic acid showed the most typical bands. The gelatins extracted from pig skin pretreated with acetic acid and hydrochloric acid exhibited the highest gelation-melting transition temperatures (26.81/34.17 °C) and gel strength (605.278 g), respectively. 69 characteristic peptides were the same in all gelatins from pigskin pretreated by various acids. A further comparison of this work with prior studied revealed that 8 were detected under different extraction and processing conditions. These common characteristic peptides could be used as the foundation for pigskin gelatin traceability, boosting accuracy.